Edward Kronold papers - Kronold, Edward, 1899-1993.
Correspondence concerning papers to be presented at meetings of the New York Psychoanalytic Society and the International Psycho-Analytical Association in 1950 and 1957. Correspondents include Edward Bibring, Eduard Hitschmann, Melanie Klein, Ernst Kris, Richard F. Sterba, and Edoardo Weiss.
Psychoanalyst.
In English and German.
Forms part of: Sigmund Freud collection.
Keywords: Bibring, Edward, -- 1894-1959 -- Correspondence; Hitschmann, Eduard, -- 1871-1957 -- Correspondence; Klein, Melanie -- Correspondence; Kris, Ernst, -- 1900-1957 -- Correspondence; Sterba, Richard F. -- Correspondence; Weiss, Edoardo, -- 1889-1939 -- Correspondence; International Psycho-Analytical Association; New York Psychoanalytic Society; Psychoanalysis; Psychoanalysis -- Societies, etc; Psychoanalysts